1994
DOI: 10.1177/095632029400500409
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl Hydrogen Phosphonate Derivatives of the anti-HIV Agent AZT may be Less Toxic than the Parent Nucleoside Analogue

Abstract: SummaryNovel alkyl hydrogen phosphonate derivatives of the anti-HIV nucleoside analogue AZT have been prepared by phosphorochloridite chemistry. These materials are designed to act as labile membrane-soluble prodrugs of the bioactive free nucleotides. In vitro evaluation has revealed the compounds to have a pronounced and selective antiviral action. Shortchain (C1-C7) alkyl derivatives are more potent than the parent hydrogen phosphonate, whilst one longchain (C18) compound is less active. In an assay that dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A series of alkyl, i.e., ethyl, isopropyl, and tert-butyl, masked 5′-O-phosphate ester derivatives (7−9) was synthesized to evaluate their effects on the well-characterized cardioprotective effect of 1. 10 In addition, various other modifications on the atoms of the 5′-O-phosphate group of reference compound 1, such as dideutero (10), thioate (11,12), and dithioate (13), have been made in the form of diethyl esters. Finally, we also decided to evaluate the cardioprotective ability of ester analogues 14, 15, and 16 of phosphonate derivatives 2, 6, and 3, respectively.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A series of alkyl, i.e., ethyl, isopropyl, and tert-butyl, masked 5′-O-phosphate ester derivatives (7−9) was synthesized to evaluate their effects on the well-characterized cardioprotective effect of 1. 10 In addition, various other modifications on the atoms of the 5′-O-phosphate group of reference compound 1, such as dideutero (10), thioate (11,12), and dithioate (13), have been made in the form of diethyl esters. Finally, we also decided to evaluate the cardioprotective ability of ester analogues 14, 15, and 16 of phosphonate derivatives 2, 6, and 3, respectively.…”
Section: ■ Resultsmentioning
confidence: 99%
“…However, model studies of phosphotriesters and phosphonate diesters have shown that simple esters similar to our uncharged alkyl esters are not readily cleaved in vivo . 1114 Therefore, we examined the stability of representative nucleotide derivatives under biological conditions. Consistently, we were unable to demonstrate any hydrolysis of phosphonate diesters 14 and 16 under various conditions of pH extremes (1 and 11) and the presence of rat plasma or liver microsomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when phosphazide was later tested on three different cell lines (MT-4, CE M-SS and CE M-X 174), its activity was found to be lower than that of AZT by almost an order of magnitude [20]. It was reported in another paper [21] that the anti-HIV activity of compound 1 in the cell cultures C8 and JM was 10–20 times higher vs. that of AZT. Contrariwise, according to [22], the selectivity indices of H-phosphonate 1 were 1.5 and 15 times higher than those of AZT (IIIB and HXB2 strains of HIV in blood mononuclear cells were used).…”
Section: Nikavir (Phosphazide) the First Achievement In Designing Dementioning
confidence: 99%